Review of monograph - Oleh Hordunovskyi (Cхід, 2016)
Review of monograph: Malyarchuk О. М. Social and economic processes in the western region of the Ukrainian SSR (1964–1991) : [monograph] / О. М. Malyarchuk. – Ivano-Frankivsk : Symphoniia forte, 2015. – 548 p.